The role of direct air capture in achieving climate-neutral aviation - Nicoletta Brazzola; Amir Meskaldji; Anthony Patt; Tim Tröndle; Christian Moretti (Nature Communications)
Abstract Growing demand for air travel and limited scalable solutions pose significant challenges to the mitigation of aviation’s climate change impact. Direct air capture (DAC) may gain prominence due to its versatile applications for either carbon removal (direct air carbon capture and storage, DACCS) or synthetic fuel production (direct air carbon capture and utilization, DACCU). Through a comprehensive and time-dynamic techno-economic assessment, we explore the conditions for synthetic fuels from DACCU to become cost-competitive with an emit-and-remove strategy based on DACCS under 2050 CO2 and climate neutrality targets. We find that synthetic fuels could achieve climate neutrality at lower cost than an emit-and-remove strategy due to their ability to cost-effectively mitigate contrails. Under demand reductions, contrail avoidance, and CO2 neutrality targets the cost advantage of synthetic fuels weakens or disappears. Low electricity cost (€0.02 kWh-1) and high fossil kerosene prices (€0.9 l-1) can favor synthetic fuels’ cost-competitiveness even under these conditions. Strategic interventions, such as optimal siting and the elimination of fossil fuel subsidies, can thus favor a shift away from fossil-reliant aviation.